Attitudes to participation in a lung cancer screening trial: a qualitative study. Issue 5 (21st November 2011) - Patel, Deesha; Akporobaro, Ajiri; Chinyanganya, Nyasha; Hackshaw, Allan; Seale, Clive; Spiro, Stephen G; Griffiths, Chris
Abstract : Background: Earlier diagnosis of lung cancer is key to reducing mortality. New evidence suggests that smokers have negative attitudes to screening and participation in lung cancer screening trials is poor (<1 in 6 of those eligible). Understanding participation is important since uptake in screening trials is likely to predict uptake in screening programmes. A qualitative study of people accepting and declining participation in the Lung-SEARCH screening trial was conducted. Two questions were addressed: Are the screening methods offered acceptable to patients? Why do some people take part and others decline? Methods: The qualitative study used semi-structured interviews with 60 respondents from three groups: (a) trial participants providing an annual sputum sample; (b) trial participants with a sputum sample showing abnormal cytology and thus undergoing annual CT scanning and bronchoscopy; and (c) those declining trial participation. Results: Most respondents (48/60, 80%) viewed sputum provision, CT scanning and bronchoscopy as largely acceptable. Those declining trial participation described fear of bronchoscopy, inconvenience of travelling to hospitals for screening investigations and perceived themselves as having low susceptibility to lung cancer or being too old to benefit. Patients declining participation discounted their risk from smoking and considered negative family histories and good health to be protective. Four typological behaviours emerged within those declining: 'too old to be bothered', 'worriers', 'fatalists' and 'avoiders'. Conclusion: Sputum provision, CT scanning and bronchoscopy are largely acceptable to those participating in a screening trial. However, the decision to participate or decline reflects a complex balance of factors including acceptability and convenience of screening methods, risk perception, altruism and self-interest. Improving practical and changing cognitive aspects of participation will be key to improving uptake of lung cancer screening.